Challenges to Socio-Economic Balance in Istanbul’s Rapid Urbanization - Nilay H. B.; Onur S. A. (Studies in Social Science & Humanities, 2024)
Istanbul, a city of significant historical and geographical importance, has experienced rapid urbanization over the past few decades. This paper explores the socio-economic challenges that have arisen from this urban expansion, focusing on housing shortages, infrastructure strain, economic disparities, social cohesion issues, and environmental degradation. Using a mixed-methods approach, the study integrates qualitative insights from in-depth interviews and field observations with quantitative data from structured surveys and secondary sources. The findings reveal that while urban renewal projects and infrastructural investments have modernized parts of the city and attracted investment, they have also led to the displacement of long-term residents, exacerbated economic inequalities, and stressed existing infrastructure. Comparative analysis with other rapidly urbanizing cities like Mumbai, São Paulo, and Shanghai provides valuable lessons for addressing these challenges. The paper concludes with policy recommendations aimed at promoting inclusive and sustainable urban development in Istanbul, emphasizing the need for equitable housing policies, strategic infrastructural investments, community engagement, and the adoption of smart city technologies.